Large Rhinolith in Nasal Cavity and Extension to Maxillary Sinus in a Cocaine User - Delamura, Izabela F. [UNESP] (2024)
Although rhinoliths are rare, they deserve attention and should be considered in the differential diagnoses of calcified lesions that can affect the nasal cavity and maxillary sinus region. This article reports a case of a large rhinolith in the nasal cavity caused by cocaine use. Initially, the patient denied drug use, leaving several uncertainties regarding the diagnosis, including recurrent sinusitis. However, after the histopathologic results, the patient admitted to previous cocaine use, emphasizing the importance of honesty in the medical history to guide diagnostic hypotheses, as well as the awareness of the diagnostic possibility of a rhinolith to assist in treatment.